Ti-MIL-125-NH2 membrane grown on a TiO2 disc by combined microwave/ultrasonic heating: facile synthesis for catalytic application. Issue 68 (4th July 2016) - Lee, Yu-Ri; Cho, Sung-Min; Baeck, Sung-Hyeon; Ahn, Wha-Seung; Cho, Won-Seung
Abstract : A Ti-MIL125-NH2 membrane with uniform crystals was prepared on a TiO2 disc using microwave/ultrasonic irradiation, and used as a reusable catalyst for the Knoevenagel reaction. Abstract : A Ti-MIL125-NH2 membrane with a high surface coverage of uniform crystals was prepared on a TiO2 disc using a unique combination of microwave-assisted nucleation followed by ultrasonic irradiation, which produced a highly stable catalytic film for a liquid phase Knoevenagel condensation reaction.